Pengaruh Economic Value Added (EVA) dan Market Value Added (MVA) Terhadap Return Saham Pada Perusahaan Sub Sektor Tembakau Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2017 – 2022 - Tsanisa Aulia Taopik; Aninditha Putri Kusumawardhani; Dikdik Purwadisastra (LPPM UNIBI, 2023)
This study aims to determine the description and magnitude of the effect of Economic Value Added (EVA) And Market Value Added (MVA) partially or simultaneously on stock returns. The method used is descriptive and verification method with a quantitative approach The population of this study is tobacco sub sector companies listed on the indonesia stock exchange (IDX) for the period 2017 - 2022. The sample is 18 financial statements from 3 companies. The sample selection method is purposive sampling. Based on the value of the coefficient of determination of the variable Economic Value Added (EVA) on stock returns has an effect of 6,4%. The Market Value Added (MVA) variable on stock returns has an effect of 1%. The variable of Economic Value Added (EVA) and Market Value Added (MVA) on stock returns has an effect of 10,1%. The results showed : (1) Economic Value Added (EVA) has no effect and no significant effect on stock return with a t hit value of 0.793 < t tab of 2.131 and a significance of 0.440 > 0.05. (2) Market Value Added (MVA) has no effect and no significant effect on stock return with a t hit value of 0.793 < t tab 2.131 and a significance of 0.440 > 0.05. (3) Economic Value Added (EVA) and Market Value Added (MVA) which work simultaneously have a effect and no significant effect toward the stock return with an F hit value of 0.846 < F tab 3.739 and a significance of 0.449 > 0.05.